Indigenous Traditional Medical Practitioners’ Lack of Formal Medical Education Impacts their Choices of Information Resources for the Treatment of Sickle Cell Anemia - Melssen, Maria (Evidence Based Library and Information Practice, 2011)
Objective – To determine the information seeking behaviours of traditional medical practitioners who treat sickle cell anemia patients. Design – Qualitative, interviewer-administered, structured questionnaire. Setting – City and surrounding rural area of Ibadan, Nigeria. Subjects – The researchers selected for this study 160 indigenous traditional medical practitioners who specialize in the treatment of sickle cell anemia. The majority of the subjects were male, with 96 male and 64 female. The practitioners were selected from four traditional medical practitioner associations in Ibadan, Nigeria. The researchers met with the leaders of the four organizations and identified which of the 420 members specialize in the treatment of sickle cell anemia. Methods – The subjects were asked survey questions orally during face-to-face interviews. The decision to conduct interviews and ask the survey questions orally (rather than having the subjects complete the survey questions on their own) was based on the perceived low literacy level of the traditional medical practitioners. Survey questions were written using the analytical framework of Taylor’s information use environment model. According to the authors, the premise of Taylor’s information use environment model is that individuals can be grouped according to their “professional and/or social characteristics” (p. 124). The group is then characterized by the members’ approach to problem solving: the type of problems they encounter, the setting they find themselves in during the problem, and how the group as a whole determines what course of action needs to be taken in order to solve the problem. The problem solving strategy of the group impacts its need for information and how that information is located and used. The questions asked by the researchers fell into one of five research areas: • the environment of the group • the diagnosis and treatment methods of traditional medical practitioners and how they obtain information that shapes their diagnosis and treatment choices • sources of information for the treatment of sickle cell anemia and the factors that encourage or discourage the use of those sources • how information about sickle cell anemia is communicated amongst the traditional medical practitioners • the extent to which orthodox and traditional approaches to the treatment of sickle cell anemia are integrated. All 160 subjects completed the interview and all of the surveys were determined to be usable. Main Results – The main sources of professional knowledge and training of the traditional medical practitioners are their fathers (55%) and master healers (42.5%). This knowledge is orally preserved: none of the respondents completed a formal training program at a university. The information used to select the best treatment options for patients with sickle cell anemia is the patient’s diet or eating habits (62%) and new traditional remedies (55%). New traditional remedies are defined by the authors as “the location and potency of herbs, roots, bark and parts of animals used to compound drugs or make ritual sacrifices” (p. 128). The information found least useful by the traditional practitioners is the authenticity of new remedies (20%). The traditional practitioners would wait for their patients to report back regarding the success or failure of the treatment they were provided. The researchers also discovered that traditional practitioners rarely, if ever, share their diagnosis and treatment methodologies with other practitioners. The diagnostic tests for sickle cell anemia used most often by traditional practitioners are visual observation (32.5%) and history taking (48%). Only a fraction of the practitioners (10%) utilize “orthodox methods” which include Hb electrophoresis. The treatment option of choice by the majority of practitioners is concoctions (62.5%). The traditional practitioners favour informal sources of information over formal sources. The informal sources most commonly used are local associations (55%), colleagues (55%), and master healers (52.5%). Such formal resources as medical journals, seminars or workshops, the Internet, and libraries are rarely if ever used. The factors influencing the practitioners’ resource choice include relevance (87.8%), suitability (70%), and availability (67.5%). Many practitioners also refer their patients to other traditional medical practitioners; however, very few (27.5%) refer patients to orthodox physicians. The traditional practitioners felt that they can treat their patients on their own and do not need the orthodox physician’s help. The traditional practitioners also feel that there is little or no information sharing between the traditional practitioners and the orthodox physicians: the only time information is exchanged between the two groups is when the orthodox physicians want to conduct research on traditional medical practices. Conclusion – The traditional practitioners rely heavily on information from local experts to guide their treatment plans for sickle cell anemia patients. The success or failure of a given treatment plan is also based on what did or did not work in the past. These practitioners do not have a formal education and have a low literacy level. This group is not recognized by western medical culture as a result of their lack of professional, western medical training. Another issue is that there is not a solid documentation system of the treatment and management of sickle cell anemia by this group. This is due to their fears of having their methods “stolen” by fellow practitioners. Recommendations by the authors include having the association leaders document and track the treatment and disease management methods used by their members and implementing a training program for the indigenous traditional medicine practitioners. Further research needed includes exploring the various ways to integrate western medical practices with traditional practices as well as investigating ways to encourage collaboration and sharing of information between indigenous medical practitioners.